(untitled) (Islas, 2024)
Introduction: The poetry book Los Rembrandt de L´Hermitage (1992) by Fina García Marruz is analyzed as a «practice of non-belonging», a concept proposed by Florencia Garramuño (2015), specifically the practice of the «empire of the senses». Methods: The critical-interpretive methodology of Florencia Garramuño’s thought, which is based on the thinking of Jacques Rancière, was used to conduct a text analysis. Results: Each poem is characterized to argue that the poetry collection is configured as an empire of the senses through ekphrasis. Conclusions: The poetry book reconfigures the sensible through the dissolution of inside/outside, contemplation/action, divine/human, extraordinary/ordinary, by exploring the paintings that cause a feeling as sensation and as emotion.